2014
DOI: 10.1111/1574-6941.12407
|View full text |Cite
|
Sign up to set email alerts
|

A dietary polyunsaturated fatty acid improves consumer performance during challenge with an opportunistic bacterial pathogen

Abstract: A dietary deficiency in polyunsaturated fatty acids (PUFAs) and/or sterols can severely constrain growth and reproduction of invertebrate consumers. Single nutrients are potentially assigned to different physiological processes, for example to support defence mechanisms; therefore, lipid requirements of healthy and pathogen-challenged consumers might differ. In an oral exposure experiment, we explored the effects of dietary PUFAs and cholesterol on growth, reproduction and survival of an aquatic key herbivore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…Furthermore, we observed an increase in the somatic growth rate of D. magna when ARA was supplied. This is in line with the results from Schlotz et al (), who observed higher growth rates of D. magna fed with an ARA‐enriched food mixture of A. obliquus and S. elongatus compared to a C 20 ‐PUFA‐free diet. Becker and Boersma () also observed an increase in somatic growth of D. magna when ARA was supplemented to P‐sufficient A. obliquus and provided an ARA threshold (lowest ARA concentration at which the growth of D. magna was not limited) of only 0.06 mg g −1 dry mass which corresponds to approximately 0.136 μ g ARA mg POC −1 when a conversion factor of dry mass to carbon of 0.44 is used (Becker and Boersma , ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, we observed an increase in the somatic growth rate of D. magna when ARA was supplied. This is in line with the results from Schlotz et al (), who observed higher growth rates of D. magna fed with an ARA‐enriched food mixture of A. obliquus and S. elongatus compared to a C 20 ‐PUFA‐free diet. Becker and Boersma () also observed an increase in somatic growth of D. magna when ARA was supplemented to P‐sufficient A. obliquus and provided an ARA threshold (lowest ARA concentration at which the growth of D. magna was not limited) of only 0.06 mg g −1 dry mass which corresponds to approximately 0.136 μ g ARA mg POC −1 when a conversion factor of dry mass to carbon of 0.44 is used (Becker and Boersma , ).…”
Section: Discussionsupporting
confidence: 92%
“…As both ARA and EPA serve as precursors for eicosanoids (Heckmann et al , b ; Schlotz et al ; Garreta‐Lara et al ), they play an important role for Daphnia ’s reproduction and the immune system (Martin‐Creuzburg et al ; Schlotz et al ; Fink and Windisch ). For example, ARA was shown to improve the survival and reproduction of D. magna exposed to an opportunistic bacterial pathogen (Schlotz et al ). However, in vertebrates, ARA‐ and EPA‐derived eicosanoids have partially opposing effects, where their proinflammatory and anti‐inflammatory activity, respectively, serves as the best example (Schmitz and Ecker ; Alcock et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on annual averages, the contribution of cyanobacteria to total phytoplankton biomass never exceeded 13.5% (1972), and regarding summer means (May–October), cyanobacteria never represented more than 25.6% (1972) of total phytoplankton biomass, though their relative contribution was presumably much higher during the peak of cyanobacterial blooms (Güde & Straile, ). Supplementation experiments with nontoxic cyanobacteria suggest that Daphnia are limited by sterols when at least 30% of the total provided carbon is represented by cyanobacteria (von Elert et al, ; Martin‐Creuzburg et al, ; Schlotz, Pester, Freese, & Martin‐Creuzburg, ). It is thus possible that phytoplankton in Lake Constance always provided enough phytosterols that could be metabolized into cholesterol to prevent a limitation by sterols and to ensure sufficient cholesterol allocation into the resting eggs.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the fecundity of Daphnia can be increased by supplementing the eicosanoid precursors ARA and EPA, implying that eicosanoid biosynthesis is linked to reproduction (Martin-Creuzburg et al, 2010;Schlotz et al, 2013). Moreover, it has been shown recently that the dietary PUFA supply can improve the performance of Daphnia magna under pathogen challenge, suggesting a link between eicosanoid biosynthesis and immunity (Schlotz et al, 2013(Schlotz et al, , 2014. These latter studies also proposed that the presence of eicosanoid precursors (i.e.…”
Section: Introductionmentioning
confidence: 97%